Impact Evaluation of Conflict Prevention and Peacebuilding Interventions - Gaarder, Marie; Annan, Jeannie (World Bank, Washington, DC, 2013)
The international community is paying increased attention to the 25 percent of the world's population that lives in fragile and conflict affected settings, acknowledging that these settings represent daunting development challenges. To deliver better results on the ground, it is necessary to improve the understanding of the impacts and effectiveness of development interventions operating in contexts of conflict and fragility. This paper argues that it is both possible and important to carry out impact evaluations even in settings of violent conflict, and it presents some examples from a collection of impact evaluations of conflict prevention and peacebuilding interventions. The paper examines the practices of impact evaluators in the peacebuilding sector to see how they address evaluation design, data collection, and conflict analysis. Finally, it argues that such evaluations are crucial for testing assumptions about how development interventions affect change -- the so-called "theory of change" -- which is important for understanding the results on the ground.